2011
DOI: 10.1111/j.1464-410x.2010.10002.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ultrasonography as an adjunct to fluoroscopy for renal access in percutaneous nephrolithotomy (PCNL)

Abstract: Study Type – Therapy (case series) Level of Evidence 4 OBJECTIVE • To evaluate the safety and efficacy of ultrasonography (US)‐guided renal access in percutaneous nephrolithotomy (PCNL), as compared with conventional fluoroscopy‐guided renal access in a prospective randomized trial. PATIENTS AND METHODS • From January 2008 to October 2009, 224 patients with renal calculi undergoing PCNL were randomized into two groups. • Group 1 (112 patients) underwent PCNL using only fluoroscopy‐guided renal access; while in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 22 publications
5
77
1
5
Order By: Relevance
“…Access to the renal collecting system from the most suitable calyx can be established either under fluoroscopic and/or sonographic guidance. Main aim of these two different guiding procedures should be a direct path which will be identified and used from the skin through the papilla of the desired calyx (14). Accumulated experience so far has clearly demonstrated that each of these methods could be associated with certain advantages as well as disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Access to the renal collecting system from the most suitable calyx can be established either under fluoroscopic and/or sonographic guidance. Main aim of these two different guiding procedures should be a direct path which will be identified and used from the skin through the papilla of the desired calyx (14). Accumulated experience so far has clearly demonstrated that each of these methods could be associated with certain advantages as well as disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 A randomized prospective trial comparing outcomes of ultrasound-guided PCNL access to traditional fluoroscopic access in 224 patients demonstrated increased accuracy of puncture, fewer number of puncture attempts, shorter operative time, and reduced radiation exposure time, with similar rates of procedural success and length of hospital stay for the ultrasound group. 7 In another study, urology residents undergoing PCNL training were able to achieve decreased radiation exposure time and higher accuracy of puncture for pure ultrasound-guided PCNL, although 6 of 32 patients required fluoroscopic adjustment. 12 In a singlecenter study of 700 patients who underwent complete ultrasound-guided PCNL in China, 92.6% of patients with a single calculus and 82.9% of patients with staghorn or multiple stones were rendered stone free.…”
Section: Role In Urologic Practicementioning
confidence: 97%
“…5 In an effort to decrease radiation exposure, low-dose CT scans (*3 millisieverts [mSv]) and ultralow-dose CT scans (0.83 mSv) have been introduced. 6,7 Furthermore, to limit unnecessary radiation exposure to the stone patient, the American Urological Association has published imaging guidelines for the practicing urologist. 8 As a collaborative effort, the urologic community has done well in limiting radiation exposure through advancements in Department of Urology, Mayo Clinic, Rochester, Minnesota.…”
Section: Author Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have demonstrated the feasibility of utilizing ultrasound as an imaging modality during PCNL, operating on mean stone burdens ranging from 2-6 cm, producing a 63 % to 100 % stone-free rate [78][79][80][81][82]. Limitations of using ultrasound as the sole technique for access include the limited use in obese patients, those with full staghorn calculi, and those lacking hydronephrosis, due to reduced visibility.…”
Section: Reducing Radiation During Percutaneous Nephrolithotomymentioning
confidence: 99%